Representing a conceptual model for integrating Project Management Information Systems in project-based organizations - Saeed Ghorbani; Aboutaleb Shafaghat (goodwood publishing)
Purpose: This paper aimed to introduce a comprehensive model for integrating project management information systems in project-based organizations. Research methodology: The proposed model is presented hierarchically through a comprehensive literature review and a review of several national projects in Iran. Validation of this model was done in two ways. On the one hand, expert opinions were asked about it through several interviews. On the other hand, the model was used in some national projects and its deficiencies were identified. Finally, the necessary modifications were made to the model. Results: In this study, it became clear that a comprehensive, integrated project management information system at its macro level should consist of three subsystems, including project warden, project administrator and project employer that mutual exchange of information should be done well between them. It was also found that this mutual information exchange should also exist among the components of each of these subsystems. Limitation: This research only described in project based organizations. Contribution: The Project Management Information System (PMIS) model provided in this research is the most comprehensive models in this scope for project-based organizations that have considered all aspects of project management. Keywords: Project management, PMIS, Project-based organizations, Integrated model